Gambaran Karies Gigi pada Penyandang Diabetes Melitus di Rumah Sakit Kalooran Amurang - Ampow, Falen V.; Pangemanan, Damajanty H. C.; Anindita, Pritartha S. (Universitas Sam Ratulangi, 2018)
Abstract: Dental caries is caused by certain bacteria that have acid-forming properties. Due to these bacteria, a low pH in the oral cavity is achieved which may cause slow enamel demineralization and form a ferocious focus. Diabetes mellitus (DM), a metabolic disorder characterized by hyperglycemia, is one of the predisposing factors of dental caries. This study was aimed to obtain the profile of dental caries in people with diabetes mellitus. This was a descriptive study with a cross sectional design. Subjects were diabetic patients at the Internal Medicine Department of Kalooran Hospital Amurang. There were 50 patients in this study obtained by using total sampling technique. Diabetic status was determined by using random blood glucose level (Perkeni 2011) meanwhile caries status was assessed by using DMF-T score. Data were processed by using SPSS and then were presented in tabular form. The results showed that very high caries index was found in 16.0% of subjects with good blood glucose control, 30.0% with moderate blood glucose control, and 36.0% with poor blood glucose control; the total number was 82.0% of subjects. Most subjects had diabetes for 5-10 years (44.0%) with very high caries index (40.0%). Conclusion: Most diabetic patients had very high caries index with the highest percentage in patients with DM for 5-10 years and in patients with poor blood glucose control.Keywords: diabetes mellitus, blood glucose level, dental cariesÂ Abstrak: Karies gigi terjadi oleh karena bakteri-bakteri tertentu yang mempunyai sifat membentuk asam sehingga terjadi pH rendah yang dapat menyebabkan pelarutan mineral enamel secara perlahan dan membentuk fokus perlubangan. Diabetes melitus (DM) yang ditandai dengan keadaan hiperglikemia merupakan salah satu faktor predisposisi terjadinya karies. Penelitian ini bertujuan untuk mengetahui gambaran karies gigi pada penyandang DM. Jenis penelitian ialah deskriptif dengan desain potong lintang. Subjek penelitian ialah penyandang DM di Poliklinik Penyakit Dalam RS Kalooran Amurang yang berjumlah 50 orang, diambil dengan teknik total sampling. Status DM dinilai melalui kadar glukosa darah sewaktu (Perkeni 2011), sedangkan status karies dinilai menggunakan skor DMF-T. Data diolah menggunakan SPSS kemudian disajikan dalam bentuk tabel. Hasil penelitian menda-patkan kategori indeks karies sangat tinggi ditemukan pada 16,0% subyek dengan kontrol gula darah baik, 30,0% dengan kontrol gula darah sedang, dan 36,0% dengan kontrol gula darah buruk; jumlah total 82,0% subyek. Subjek terbanyak ialah penyandang DM 5-10 tahun (44,0%) dengan kategori indeks karies sangat tinggi (40,0%). Simpulan: Sebagian besar penyandang DM memiliki kategori indeks karies sangat tinggi dengan persentase tertinggi pada penyandang DM 5-10 tahun dan penyandang DM dengan kontrol gula darah yang buruk.Kata kunci: diabetes melitus, kadar gula darah, karies gigi